Genome-wide characterization of genetic diversity and breed discrimination markers in Tharparkar cattle - Anal Bose; Nishu Bharia; Sonali Sonejita Nayak; Divya Rajawat; Pallavi Hembrom; Vijay Kumar; Sita Ram Gupta; Manjit Panigrahi (Mammalian Genome, 2026)

Response Surface Optimization for enhanced keratinase production from Bacillus vallismortis Gz4 isolated from poultry farm of Ghaziabad and its antifungal activity - Varsha Thadiyan; Nivedita Sharma; Divya Sharma; Vibhuti Sharma; Reena Gupta (Biocatalysis and Agricultural Biotechnology, 2026)

Multilayered regulation of Fe excess stress and the role of ascorbate in rice - Mayur Patel; Divya Gupta; Raj Kishan Agrahari; Kamiya Takehiro; Petra Bauer; Sanjib Kumar Panda (Protoplasma, 2026)

Genome-wide identification and characterization of B3 superfamily in Cucumis melo (L.) and their expression profiling under fruit development and biotic stress - Vasundhra Singh; Divya Gupta; Swati Vaish; Nootan Singh; Sapna Sharma; Ankita Srivastava (Vegetos, 2026)

Green Synthesis of ZnO-Polyaniline Nanocomposite using Syzygium cumini Leaf Extract for Ni(II) and Pb(II) Removal from Aqueous Solutions: A Comprehensive Study - Divya Bhushan; Renuka Gupta (Water, Air, & Soil Pollution, 2026)

Cloning and Heterologous Expression of Laccase from Beauveria pseudobassiana PHF4 in E. coli and its Application in the Degradation of Catechol - Divya Sharma; Sudha Batta; Ajay Kumar Thakur; Reena Gupta (Current Microbiology, 2026)

Development and evaluation of ‘Quick TB DNA Extraction’ kit for the rapid and efficient detection of multidrug-resistant tuberculosis from sputum transported on bio-safe filter - Rakesh Kumar Gupta; Keerti Chauhan; Ritu Singhal; Divya Anthwal; Vithal Prasad Myneedu; Khalid Umar Khayyam; Sangeeta Choudhary; Ashawant Gupta; Nalini Kant Gupta; Manjula Singh; Jaya Sivaswami Tyagi; Manpreet Bhalla; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Role of FTIR in the physico-chemical characterization of nanoparticles - Amar Kumar; Meenakshi; Divya Sinha; Darshan Singh; Maneesh Kumar Gupta; Nisha Saxena; Kumari Seema; Bablu Kumar; Ghanshyam Upadhyay; Manoj Kumar; Anuradha (Next Research, 2026)

Foliar Application of Biogenically Synthesized Silica Nanoparticles Improves Growth, Photosynthetic Pigments, and Soil Enzymatic Activities in Maize (Zea mays) Plants - Divya Siwach; Anu Gupta (Journal of Soil Science and Plant Nutrition, 2026)

Endocrine disruptors in aquatic environments: evaluating the toxicity of Bisphenol-A and diethyl phthalate - Divya Bajaj; Soma Mondal Ghorai; Priyanka Aggarwal; Sakshi Dua; Shobhna Gupta; Swastik Gupta; Tisha Raheja; Yash Sharma (Ecotoxicology, 2026)

Regional distribution and seasonal histomorphology of cell types of pars distalis adenohypophysis of Gaddi goats: A comparative study between the year 2001 and the present in the context of climate change - Arjun Kumar Rao; Virender Pathak; Rajesh Rajput; Divya Gupta; Parul Shukla (Tropical Animal Health and Production, 2026)

Sulforaphane-Mediated Multitarget Therapeutic Effects in Methylmercury-Induced ALS-Like Pathology: Comparative Analysis and Multifaceted Approach to Neuroprotection and Systemic Recovery - Ritam Mukherjee; Sidharth Mehan; Divya Choudhary; Ravi Rana; Ghanshyam Das Gupta; Rajaram Samant; Manoj Tongra (Molecular Neurobiology, 2026)

Comparison of clinical, radiological and outcome parameters in patients with progressive multifocal leukoencephalopathy (PML) with and without HIV infection: a cohort study - Farsana Mustafa; Anuj Ajayababu; Ajay Garg; Megha Brijwal; Divyani Garg; Manish Soneja; Aashish Choudhary; Lalit Dar; Shariq A. Shah; Venugopalan Y Vishnu; Animesh Ray; Neeraj Nischal; et al. (Journal of NeuroVirology, 2025)

Dual near-infrared wavelength photobiomodulation accelerates transdermal burn wound repair via anti-inflammatory, pain relief and redox-regulating mechanisms - Ashok Priyadarshi; Gaurav K. Keshri; Divya Yadav; Asheesh Gupta (Journal of Photochemistry and Photobiology B: Biology, 2025)

Green biocatalysis: coconut fibre-immobilized laccase in efficient degradation of tannic acid - Divya Sharma; Varsha Thadiyan; Reena Gupta (Folia Microbiologica, 2025)

Leaf miRNAs of Withania somnifera Negatively Regulate the Aging-Associated Genes in C. elegans - Shilpi Yadav; Ravi Kr. Gupta; Sailendra Kumar; Anamta Rizvi; Divya Tyagi; Aruna Satish; Digvijay Verma; Akanksha Vishwakarma; Sangeeta Saxena (Molecular Neurobiology, 2025)

Green synthesis and adsorption performance of Eucalyptus globulus leaf modified iron oxide-graphene oxide nanocomposite for Cd(II) and Pb(II) removal from aqueous solution - Divya Bhushan; Renuka Gupta (Environmental Geochemistry and Health, 2025)

Co-delivery of Exemestane and Genistein via Chitosan Coated Liposomes for Enhanced Antitumor Effect and Bone Loss Prevention in Breast Cancer Therapy: In Vivo Evaluation - Shwetakshi Sharma; S. M. Kawish; Priya Gupta; Shreshta Jain; Shahnawaz Ahmad; Zeenat Iqbal; Divya Vohora; Kanchan Kohli (AAPS PharmSciTech, 2025)

Sustainable Agriculture in Food Security Integrating Satellite Data Risk Assessment by Cyberattack Detection: AI Applications - M. Prema Kumar; N. Krishnammal; Manu Gupta; Mairaj Unisa Begum; Sameera Sultana; Divya Priya Degala (Remote Sensing in Earth Systems Sciences, 2025)

Interaction Effects of Different Fertigation Levels and Cultivars On Growth, Yield, Quality and Leaf Nutrient Content of Strawberry (Fragaria × Ananassa Duch) Under Protected Cultivation - Neelam Devi; Yogendra Singh; Divya Slathia; Govind Gupta; Shubham Pareek; Suman Kumari; Deepak Kher; Vikash Prasad Mishra; Anchal Daroch; Neha Kumari (Applied Fruit Science, 2025)

Natural products as drug leads: exploring their potential in drug discovery and development - Kuldeep Singh; Jeetendra Kumar Gupta; Dilip Kumar Chanchal; Manoj Gangadhar Shinde; Shivendra Kumar; Divya Jain; Zainab M. Almarhoon; Asma M. Alshahrani; Daniela Calina; Javad Sharifi-Rad; Anjali Tripathi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Identifying leverage points for sustainability in India’s shark supply chains - Trisha Gupta; Divya Karnad; Rodrigo Oyanedel; Hollie Booth; Tejaswi Abhiram; Harsha Gaonkar; E.J. Milner-Gulland (Marine Policy, 2025)

Allometric scaling and carbon sequestration in agroforestry species of the Western Himalayas: a model-based approach - Megha VR; R. Kaushal; Sadikul Islam; Uday Mandal; Harsh Mehta; Rajkumar; J. M. S. Tomar; Anand Kumar Gupta; Anupam Barh; Vishwal Madhav P; Vibha Singhal; Rajiv Pandey; et al. (Environmental Monitoring and Assessment, 2025)

Operational feasibility and multi-centric evaluation of ‘TB Detect sputum microscopy kit’ for the direct detection of Mycobacterium tuberculosis in field settings - Keerti Chauhan; Rakesh Kumar Gupta; Divya Anthwal; Nikita Panwalkar; Prabha Desikan; Manpreet Bhalla; Ritu Singhal; Vithal Prasad Myneedu; Khalid Umar Khayyam; Siva Kumar Shanmugam; K. Silambu Chelvi; A. Radhakrishnan; et al. (Infectious Diseases, 2024)

Fostering forest commoning for rural livelihoods: Case of gram sabha federations in Vidarbha, India - Gautam Prateek; Divya Gupta (Forest Policy and Economics, 2024)

Gene Editing: Paving the Way for Enhancing Plant Tolerance to Abiotic Stresses-Mechanisms, Breakthroughs, and Future Prospects - Divya Gupta; Amita Saini; Christell van der Vyver; Sanjib Kumar Panda (Journal of Plant Growth Regulation, 2024)

Plant biomass-based nanoparticles for remediation of contaminants from water ecosystems: Recent trends, challenges, and future perspectives - Divya Bhushan; Sachin Shoran; Rakesh Kumar; Renuka Gupta (Chemosphere, 2024)

Chemical composition of γ-irradiated German chamomile (Matricaria recutita L.) flower essential oils, acetylcholinesterase inhibitory activity and effects on growth inhibition of Staphylococcus aureus and Candida albicans - Yatish Pant; Shubham Srivastava; R.K. Lal; Anand Mishra; Laldingngheti Bawitlung; Divya Bhatt; Pankhuri Gupta; Sakshi Yadav; D.U. Bawankule; Vidushi Tyagi; Anirban Pal; C.S. Chanotiya (Biocatalysis and Agricultural Biotechnology, 2024)

Laccase: exploring structural insights and functional versatility for applications - Divya Sharma; Reena Gupta (Biologia, 2024)

Bioinformatics characterisation of B3 DNA superfamily in bitter gourd (Momordica charantia) L.and its expression in different tissues development and biotic stresses - Vasundhra Singh; Dr. Neelam Misra; Divya Gupta; Swati Vaish; Nootan Singh (South African Journal of Botany, 2024)

Time–frequency characterization of seasonal temperature in India and teleconnection of temperature with atmospheric oscillation indices - Hareesh Kumar; Nitin Joshi; Himanshu Sharma; Divya Gupta; Shakti Suryavanshi (Stochastic Environmental Research and Risk Assessment, 2024)

Bacterial diversity and enzymatic activities in poplar chronosequence: Implications for soil carbon dynamics in a semi-arid ecosystem - Sandeep Sharma; Pritpal Singh; Nihar Gupta; Divya Utreja; Ramesh Chand Kasana (Forest Ecology and Management, 2024)

Biofabrication and Characterization of Silica-coated Zinc Oxide Nanocomposite: A Sustainable Approach in Remediation of Cr(VI) Contaminated Wastewater - Divya Bhushan; Renuka Gupta (Water, Air, & Soil Pollution, 2024)

MYCN immunohistochemistry as surrogate marker for MYCN-amplified spinal ependymomas - Divya Mohan; Aruna Nambirajan; Rafat Malik; Agrima Sharma; Vaishali Suri; Kavneet Kaur; Ramesh Doddamani; Ajay Garg; Subhash Gupta; Supriya Mallick; Mehar Chand Sharma (Human Cell, 2024)

Direct Detection of Fluoroquinolone Resistance in Sputum Samples from Tuberculosis Patients by High Resolution Melt Curve Analysis - Rakesh Kumar Gupta; Divya Anthwal; Manpreet Bhalla; Jaya Sivaswami Tyagi; Sangeeta Choudhary; Sagarika Haldar (Current Microbiology, 2024)

Genome-wide identification and characterization of ABC transporter superfamily in the legume Cajanus cajan - Mridula Sanjana Mall; Shreya Shah; Shivani Singh; Namita Singh; Nootan Singh; Swati Vaish; Divya Gupta (Journal of Applied Genetics, 2023)

Dissecting the Relationship Between Neuropsychiatric and Neurodegenerative Disorders - Rohan Gupta; Dia Advani; Divya Yadav; Rashmi K Ambasta; Pravir Kumar (Molecular Neurobiology, 2023)

Genome-wide identification and expression analysis of the Pisum sativum (L.) APETALA2/ethylene-responsive factor (AP2/ERF) gene family reveals functions in drought and cold stresses - Trishna Jarambasa; Preetom Regon; Sabnoor Yeasrin Jyoti; Divya Gupta; Sanjib Kumar Panda; Bhaben Tanti (Genetica, 2023)

Novel Biocompatible Green Silver Nanoparticles Efficiently Eliminates Multidrug Resistant Nosocomial Pathogens and Mycobacterium Species - Shahbaz Aman; Narinder Kaur; Divya Mittal; Deepanjali Sharma; Komal Shukla; Bharat Singh; Anchita Sharma; Samarjeet Singh Siwal; Vijay Kumar Thakur; Hemant Joshi; Raju Gupta; Reena V. Saini; et al. (Indian Journal of Microbiology, 2023)

Genome-wide identification and characterization of glutathione S-transferase gene family in Musa acuminata L. AAA group and gaining an insight to their role in banana fruit development - Swati Vaish; Reshma Parveen; Divya Gupta; Mahesh Kumar Basantani (Journal of Applied Genetics, 2022)

Understanding precipitation characteristics of Afghanistan at provincial scale - Shakti Suryavanshi; Nitin Joshi; Hardeep Kumar Maurya; Divya Gupta; Keshav Kumar Sharma (Theoretical and Applied Climatology, 2022)

Computational insights into diverse aspects of glutathione S-transferase gene family in Papaver somniferum - Swati Vaish; Reshma Parveen; Rajneesh; Nootan Singh; Divya Gupta; Mahesh Kumar Basantani (Journal of Plant Research, 2022)

Signaling molecules hydrogen sulfide (H2S) and nitric oxide (NO): role in microalgae under adverse environmental conditions - Garima Singh; Anuradha Patel; Sanjesh Tiwari; Divya Gupta; Sheo Mohan Prasad (Acta Physiologiae Plantarum, 2022)

Coping with the ‘Indian summer’: unique nesting cycle and nest architecture of the paper wasp, Polistes wattii - Ruchira Sen; Kunika Malhotra; Manisha Gupta; Rajbir Kaur; Divya Bawa; Meghna Duhan; Sonia Sandhi; Pratibha Songara; Deepak Nain; Rhitoban Raychoudhury (The Science of Nature, 2022)

A decision support tool for integrated fisheries bycatch management - Eric Gilman; Martin Hall; Hollie Booth; Trisha Gupta; Milani Chaloupka; Hannah Fennell; Michel J. Kaiser; Divya Karnad; E. J. Milner-Gulland (Reviews in Fish Biology and Fisheries, 2022)
Participatory decision tools enable stakeholders to reconcile conflicting natural resources management objectives. Fisheries targeting highly productive species can have profound impacts on co-occurring bycatch species with low fecundity and other life history traits that make them vulnerable to anthropogenic sources of mortality. This study developed a decision tool for integrated bycatch management for data-limited to data-rich fisheries, improving upon current piecemeal approaches. First, through a systematic literature review, participants compile a comprehensive database of methods to mitigate the catch and fishing mortality of threatened bycatch species. These mitigation methods are then categorized into tiers of a sequential mitigation hierarchy, where interventions that avoid capture are considered before those that minimize catchability, followed by methods that minimize fishing mortality, before approaches that offset residual impacts. The methods are also assembled within an evidence hierarchy, where findings from meta-analytic modelling studies are more robust and generalizable than from individual studies. The decision tool enables stakeholders to evaluate alternative bycatch management strategies’ efficacy at meeting specific and measurable objectives for mitigating the catch and mortality of bycatch and for costs from multispecies conflicts, economic viability, practicality and safety, while accounting for the fishery-specific feasibility of compliance monitoring of alternative bycatch management measures. Ongoing adaptation of the bycatch management framework addresses findings from performance assessments, updated evidence, new mitigation methods and changes to governance systems. The proposed decision tool therefore enables stakeholders to develop bycatch management frameworks that provide precautionary protection for the most vulnerable populations with acceptable tradeoffs.

5-aminolevulinic acid (ALA) regulates photosynthetic performance and nitrogen metabolism status in UV-B challenged Cajanus cajan L. seedlings - Divya Gupta; Sheo Mohan Prasad (Journal of Plant Biochemistry and Biotechnology, 2022)

Role of neurotransmitters in the regulation of cutaneous wound healing - Divya Gupta; Dhirender Kaushik; Vandana Mohan (Experimental Brain Research, 2022)

A review on degradation of organic dyes by using metal oxide semiconductors - Sapna Yadav; Kriti Shakya; Aarushi Gupta; Divya Singh; Anjana R. Chandran; Anjali Varayil Aanappalli; Kanika Goyal; Nutan Rani; Kalawati Saini (Environmental Science and Pollution Research, 2022)

Bioinformatics characterization of patatin-related phospholipase A (pPLA) gene family in agriculturally important crops viz Vigna radiata, Vigna angularis, and Glycine max - Reshma Parveen; Swati Vaish; Divya Gupta; Mahesh K. Basantani (Biologia, 2022)

The Origin and Clinical Relevance of Yoga Nidra - Seithikurippu R. Pandi-Perumal; David Warren Spence; Neena Srivastava; Divya Kanchibhotla; Kamakhya Kumar; Gaurav Saurabh Sharma; Ravi Gupta; Gitanjali Batmanabane (Sleep and Vigilance, 2022)

Direct Molecular Detection of Drug-Resistant Tuberculosis from Transported Bio-Safe Dried Sputum on Filter-Paper - Divya Anthwal; Shaina Jamwal; Rakesh Kumar Gupta; Ritu Singhal; Ajoy Kumar Verma; Manpreet Bhalla; Vithal Prasad Myneedu; Rohit Sarin; Sangeeta Choudhary; Jaya Sivaswami Tyagi; Sagarika Haldar (Current Microbiology, 2022)

Eumycetoma of the Foot due to Fusarium solani in a Person with Diabetes Mellitus: Report of a Case and Review of Literature - Liza Das; Divya Dahiya; Kirti Gupta; Mahesh Prakash; Bhanu Malhotra; Ashu Rastogi; Hansraj Choudhary; Shivaprakash M. Rudramurthy; Pinaki Dutta (Mycopathologia, 2021)

Optical Clearing of Skeletal Muscle Bundles Engineered in 3-D Printed Templates - Nethika R. Ariyasinghe; Jeffrey W. Santoso; Divya Gupta; Mark J. Pincus; Paul R. August; Megan L. McCain (Annals of Biomedical Engineering, 2021)

Obstructive Sleep Apnea Comorbid with Late-Onset Kleine–Levin Syndrome: A Rare Condition - M. P. Divya; Akash Kumar; Shivam Gupta; Sudheer Tale; Lokesh Kumar Saini; Ravi Gupta (Sleep and Vigilance, 2020)

Fine particulate pollution and ambient air quality: A case study over an urban site in Delhi, India - Janhavi Singh; Priyanshu Gupta; Deepak Gupta; Sunita Verma; Divya Prakash; Swagata Payra (Journal of Earth System Science, 2020)

Specific H+ level is crucial for accurate phosphate quantification using ascorbate as a reductant - Subramaniyan Divya; Peddisetty Sharmila; J. Dinakaran; Gupta Yamal; Kottapalli S. Rao; P. Pardha-Saradhi (Protoplasma, 2020)

Cationic cholesterol derivative efficiently delivers the genes: in silico and in vitro studies - Jasmin Monpara; Divya Velga; Tripti Verma; Sanjay Gupta; Pradeep Vavia (Drug Delivery and Translational Research, 2019)

Serum Mortalin Correlated with α-Synuclein as Serum Markers in Parkinson’s Disease: A Pilot Study - Amrendra Pratap Singh; Teena Bajaj; Divya Gupta; Sundararajan Baskar Singh; Avinash Chakrawarty; Vinay Goyal; Aparajit B. Dey; Sharmistha Dey (NeuroMolecular Medicine, 2018)

Escherichia coli Contamination on Ready-To-Eat (RTE), Lettuce - Divya Gupta; Chandra A. Madramootoo (Exposure and Health, 2017)

Fate and Transport of Escherichia coli in Tomato Production - Divya Gupta; Chandra A. Madramootoo (Exposure and Health, 2017)

Design and Development of Bioceramic Based Functionalized PLGA Nanoparticles of Risedronate for Bone Targeting: In-vitro Characterization and Pharmacodynamic Evaluation - Purnima Rawat; Kapil Manglani; Sarika Gupta; Abul kalam; Divya Vohora; Farhan Jalees Ahmad; Sushama Talegaonkar (Pharmaceutical Research, 2015)

Glutaredoxin-mediated selenite reduction triggers oxidative stress in Synechococcus elongatus PCC7942 cells - Bhagyashri Gupta; Mona Saggu; Divya Bagchi (Journal of Applied Phycology, 2015)

Co-localization of Disturbed Flow Patterns and Occlusive Cardiac Allograft Vasculopathy Lesion Formation in Heart Transplant Patients - Lucas H. Timmins; Divya Gupta; Michel T. Corban; David S. Molony; John N. Oshinski; Habib Samady; Don P. Giddens (Cardiovascular Engineering and Technology, 2015)

Herbs–Are they Safe Enough? An Overview - Divya Singh; Rajiv Gupta; Shubhini A. Saraf (Critical Reviews in Food Science and Nutrition, 2012)

Economics of Flood Protection in India - Sujata Gupta; Akram Javed; Divya Datt (Natural Hazards, 2003)